803 QUALITY OF LIFE IN OLDER TRAUMA PATIENTS AFTER INJURY: FINDINGS FROM THE FRAILTY IN MAJOR TRAUMA STUDY (FRAIL-T). (8th March 2022) - Jarman, H; Crouch, R; Baxter, M; Wang, C; Cole, E
Abstract: Introduction: Major trauma is a substantial health burden for older patients with a significant proportion having ongoing functional and psychological difficulties long after their injury. Frailty impacts adversely on outcome after trauma but the longer term effects are unknown. This study aimed to determine differences in health related quality of life (HRQoL) and change in dependence for frail and non-frail patients aged 65 or over discharged from Major Trauma Centres (MTCs) following injury. Methods: This prospective multi-centre study recruited from five UK MTCs between June 2019 and March 2020. Eligible patients were aged 65 or over requiring 'trauma team activation' and admitted to hospital. Follow-up data was collected via questionnaire at two time points: on day of hospital discharge and at 6 months. Primary outcome at follow-up was patient reported health-related quality of life (HRQoL) using the EQ-5D-5L measure. Results: Data were analysed from 181 patients. 54 died in the follow-up period and HRQoL data was available for 127 patients. Of these 16% were identified as frail during the trauma hospital admission using the Clinical Frailty Scale. On average, frail patients were older (82 years) compared to non-frail (77 years). HRQoL was rated similarly at discharge in both groups (Non-Frail: 60, Frail: 65, p = 0.137), but at follow-up non-frail patients reported improvement whilst those who were frail had deteriorated from the discharge base-line (Non-Frail: 70, Frail: 50, p = 0.01). At 6 months post injury, half of the frail cohort (49%) were more dependent on care than pre-trauma compared to less than a third of non-frail patients (29%). Conclusion: Patients who were frail in-hospital had worse HQRoL than non-frail patients 6 months after discharge from hospital, with increased dependence. Understanding the impact of injury on quality of life is important in planning for, and supporting, the ongoing care of frail older trauma patients.